Peran Program Dumisake Terhadap Peningkatan Pendapatan UMKM dan Perekonomian Masyarakat Provinsi Jambi Masa Covid-19 - Herlin, Faradilla; Kusmaladewi, Ovi; Dani, Rian (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this study is to determine how the Dumisake Programme affected the MSME income and the general economy of the people living in the Province of Jambi in COVID-19. This study uses a qualitative method and is descriptive in nature. The Cooperatives Service, UMK, Jambi Province served as the research site. The Dumisake Programme, a priority programme for the Jambi Provincial Government, was used to determine the research location to examine the capital assistance programme for MSMEs. The program's goals are to enhance the regional economy, lower rates of poverty and unemployment, and ultimately improve community welfare. Through the distribution of questionnaires and in-person interviews with MSME capital assistance grantees under the Jambi Provincial Government's Dumisake Programme, primary data was gathered. Legal and regulatory records, the 2021–2026 Jambi Province RPJMD, the Strategic Plan and Work Plan of the Cooperative Service, and the Jambi Province UMK serve as research supporting data for this study. Researchers conducted direct interviews with MSME players in Jambi Province who benefited from capital support under the Dumisake Programme. Data Reduction, Data Display (Data Presentation), and Conclusion Drawing/Verification (Conclusion) were the methods used for data analysis in this study. The study's findings demonstrate that the Covid-19 Pandemic had an impact on Micro, Small, and Medium-Sized Enterprises (MSMEs) that were given support by the Jambi Provincial Government. These MSMEs considered the assistance to be highly beneficial for business development, which boosted their revenue. When it comes to helping MSME players in Jambi Province with their business growth, the Jambi Provincial Government's Economic Recovery Programme has shown to be quite beneficial in providing them with products and equipment. The assistance programme has three (three) primary objectives: achieving economic recovery; enhancing MSMEs' capacity to become resilient and independent; and putting in place efficient, transparent, effective, and targeted help channels. The Cooperatives & MSMEs Service (Government) and MSME actors are the next two players engaging in the support programme for MSME actors.